2017
DOI: 10.1049/oap-cired.2017.0178
|View full text |Cite
|
Sign up to set email alerts
|

Performance indicators for quantifying the ability of the grid to host renewable electricity production

Abstract: This paper proposes a comprehensive set of performance indicators that should be used when evaluating the hosting capacity of a system. Descriptions are given for the most relevant phenomena and how they should be quantified and measured. The suggested time resolution for the data has been 1 hour, 10 min and 3 s, based on what is available already in standard meters. The use of 100, 99 or 95percentile values have an impact on the hosting capacity, and there is a need for further discussion with regards to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…As oscilações em baixa frequência são fenômenos oscilatórios que surgem em frequências próximas ao intervalo entre 0,5 a 3Hz. Já as oscilações subsíncronas (SSO) indicam uma volubilidade em frequências que variam de 5 a 55Hz, em sistemas cuja frequência fundamental é 60Hz [14].…”
Section: B Oscilações Harmônicas Em Baixa Frequênciaunclassified
“…As oscilações em baixa frequência são fenômenos oscilatórios que surgem em frequências próximas ao intervalo entre 0,5 a 3Hz. Já as oscilações subsíncronas (SSO) indicam uma volubilidade em frequências que variam de 5 a 55Hz, em sistemas cuja frequência fundamental é 60Hz [14].…”
Section: B Oscilações Harmônicas Em Baixa Frequênciaunclassified
“…Lennerhag et al [9] had studied performance indicators such as, disturbance levels of slow voltage variations, overloading, harmonics, flicker, rapid voltage changes, losses, or the number of certain power quality events in the network which can be used for evaluating the impact of renewable energy on power systems. Asadinejad et al [10] had suggested that electricity consumers should be classified and segregated based on demand response and volatility of prices under high renewable penetration which results in minimum technological and economical losses.…”
Section: Based On Performance Evaluation and Its Implications Of Renewable Energy Integration In The Power System Networkmentioning
confidence: 99%
“…As of yet, there is no complete list of phenomena and indices for hosting-capacity studies. An attempt at creating such a list is presented in [43]. With reference to Figures 1 and 2, calculating the hosting capacity requires the following tools and information:…”
Section: Other Phenomenamentioning
confidence: 99%